Additive factors do not imply discrete processing stages: a worked example using models of the Stroop task - Tom eStafford; Kevin N Gurney (Frontiers in Psychology, 2011)
Previously, it has been shown that the psychophysical law known as Pi´ eron’s Law holds for colour intensity and that the size of the effect is additive with that of Stroop condition (Stafford, Gurney & Ingram, in press). According to the additive factors method (Donders, 1868-9/1969; Sternberg, 1998), additivity is assumed to indicate independent and discrete processing stages. We present computational modelling work that demonstrates that these results can be successfully accounted for by existing single stage models of the Stroop effect. Consequently, it is not valid to infer either discrete stages or separate loci of effects from additive fac-tors. Further, our modelling work suggests that information binding may be a more important architectural property than discrete stages for producing additive factors.